PENGARUH PEMBERIAN DAUN PEPAYA (Carica papaya L) TERHADAP KINERJA PERTUMBUHAN IKAN GURAMI (Osphronemus gouramy) DAN PARAMETER FISIKA KIMIA AIR - Shinta Silvia Monalisa; Ricky Djauhari; Santa Catarina; Murrod Candra Wirabakti (Universitas Batangahari Jambi, 2022)
The aim of this research was to observe the influence of papaya leaves added to the maintenance of physical and chemical parameters of water and the growth of gouramy. The method used in this study was an experimental method with completely randomized design (CRD) of four treatments and three replications. The treatments was use papaya leaves with different concentrations which were; 0,0gr/l, 0,5gr/l, 0,7gr/l and 0,9gr/l. The results of analysis of variance (ANOVA) showed that papaya leaves given was showed significantly different for the survival rate, wight gain, specific growth rate and feed conversion ratio. The result of the study showed that treatment C get the best results on each parameters with an survival rate of 91,67%, weight gain of 2,20gr, specific growth rate of 5,32% and feed conversion ratio of 1.17 and water quality parameters the temperature in the morning is around 25,7ºC, in the afternoon is around 28,2ºC, pH ranges from 4,8-6,4, DO ranges from 1,47 mg/L- 4,34 mg/L, and amoniak is around 0,16-0,26.